2020
DOI: 10.21037/atm.2020.01.80
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the potential advantage of robotic surgical system in spleen-preserving distal pancreatectomy over conventional laparoscopic approach

Abstract: Background: This study aimed to compare success rate of spleen preservation between robotic and laparoscopic distal pancreatectomy (DP).Methods: Between November 2007 and March 2018, forty-one patients underwent the conventional laparoscopic DP (Lap group) and the other 37 patients underwent robotic DP (Robot group). The perioperative clinicopathologic variables were compared. Results:The robotic procedure was chosen by younger patients compared to conventional laparoscopic surgery (42.9±14.0 vs. 51.3±14.6 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 54 publications
1
17
1
Order By: Relevance
“…Another aspect which deserves to be highlighted among the positive impact of the RAS versus the DML on the outcomes of the distal pancreatectomy, although difficult to quantify within a cost analysis, is the higher spleen preservation rate. In this regard, our data are in line with literature [ 2 , 7 , 17 , 33 ], as the greater effectiveness of robotic system in controlling splenic vessels bleeding resulted in a higher spleen preservation rate associated with RDP among patients scheduled for spleen preservation with respect to LDP. This outcome is important not only for the biological benefit of spleen preservation, but also as the reduced use of stapler and stapler charges, necessary for the section of the splenic vessel in case of splenectomy, could contribute to reduce the CCs of RDP.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Another aspect which deserves to be highlighted among the positive impact of the RAS versus the DML on the outcomes of the distal pancreatectomy, although difficult to quantify within a cost analysis, is the higher spleen preservation rate. In this regard, our data are in line with literature [ 2 , 7 , 17 , 33 ], as the greater effectiveness of robotic system in controlling splenic vessels bleeding resulted in a higher spleen preservation rate associated with RDP among patients scheduled for spleen preservation with respect to LDP. This outcome is important not only for the biological benefit of spleen preservation, but also as the reduced use of stapler and stapler charges, necessary for the section of the splenic vessel in case of splenectomy, could contribute to reduce the CCs of RDP.…”
Section: Discussionsupporting
confidence: 91%
“…Robotic distal pancreatectomy (RDP) seems also to be associated with an additional positive impact on the clinical outcomes as well, with a reduction of conversion rates, higher spleen preservation rates, and a shorter LOS [2,6,7]. A potential barrier to the diffusion of the robotic approach could be its economic impact [8]; indeed, it is well known that RAS is generally associated with higher costs in comparison to direct manual laparoscopy (DML), also for RDP, as data emerged from previous studies, although controversial, are almost unanimously oriented toward higher cost for RAS [3,[9][10][11][12][13][14].…”
mentioning
confidence: 99%
“… 23 However, according to recent meta-analyses, 24 25 the usefulness of robots in spleen preservation was reported to be similar to that of laparoscopy, and we authors also confirmed this in previous research. 26 Rather, it was thought that the robots would be more useful in performing single-site plus one port DP, 27 28 29 30 a concept of reduced port, in well-selected patients during DP requiring concomitant splenectomy. Further research is required regarding the application of robotic surgery on DP.…”
Section: Discussionmentioning
confidence: 99%
“…The first robotic-assisted distal pancreatectomy for the treatment of p-NETs was reported in 2002 using the DaVinci ® (Intuitive Surgical, Sunnyvale, CA, USA) robotic surgical system [ 37 ]. Robotic assistance was helpful to increase the spleen preservation rate in distal pancreatectomy due to better depth perception owing to the use of three-dimensional representation, tremor elimination and seven degrees freedom of movement [ 38 , 39 ].…”
Section: Multimodal Management Of Localized Diseasementioning
confidence: 99%